2016
DOI: 10.1007/s11606-016-3612-7
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Patients' Perceptions and Use of Generic Drugs: Results of a National Survey

Abstract: BACKGROUND: Over 84 % of all prescriptions in the US are filled as generic drugs, though in prior surveys, patients reported concerns about their quality. OBJECTIVE: We aimed to survey patients' perceptions and use of generic drugs. DESIGN: Our survey (administered August 2014) assessed patients' skepticism about generic drug safety and effectiveness and how often they requested brandname drugs. Chi-square tests and two-sample t-tests assessed associations between patient demographics and the outcomes. PARTICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 23 publications
1
67
1
5
Order By: Relevance
“…Patients' or physicians' personal opinions about generic drugs also may affect their acceptance, which can indirectly affect the perceived safety and efficacy of generic drugs . For example, a 2016 national survey found that 13% of respondents believed branded drugs are more effective than generics, and 20% of respondents believed generic drugs have different adverse effects than branded drugs . In a parallel survey of physicians, 11% of physicians expressed negative perceptions about the efficacy of generic drugs, and 27% believed they caused more adverse effects .…”
mentioning
confidence: 99%
“…Patients' or physicians' personal opinions about generic drugs also may affect their acceptance, which can indirectly affect the perceived safety and efficacy of generic drugs . For example, a 2016 national survey found that 13% of respondents believed branded drugs are more effective than generics, and 20% of respondents believed generic drugs have different adverse effects than branded drugs . In a parallel survey of physicians, 11% of physicians expressed negative perceptions about the efficacy of generic drugs, and 27% believed they caused more adverse effects .…”
mentioning
confidence: 99%
“…In fact, generics actually aid long term compliance as more economical in developed countries (Shrank et al, 2006; Simoens and Sinnaeve, 2014; Barbui and Conti, 2015). In United States the vast majority (83%) agreed that physicians should prescribe generic drugs when available, however, non-Caucasian has higher brand-name drug response than Caucasian and holds much skeptical attitude to the efficacy and safety of generics (Kesselheim et al, 2016). A survey conducted in Poland showed that about 3/4 of patients preferred to use generic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although few peer‐reviewed studies on perceptions of biosimilars exist, a 2014 survey of 81 Canadian rheumatologists found that 72% were unlikely or very unlikely to offer a biologically naive patient a biosimilar over an originator biologic . Skepticism about generic drugs was also high at the time of the Hatch‐Waxman Act, and over 30 years later, about a quarter of physicians and patients remain skeptics of generics . As skepticism about generic safety and effectiveness has improved over time, so it likely will also for biosimilars after sufficient experience with them.…”
Section: Marketing Issuesmentioning
confidence: 99%